International sales law - Ferrari, Franco, 1965-; Gillette, Clayton P., 1950- (Private international law ;, 2017)
This authoritative research review presents and discusses carefully selected scholarly articles that describe and examine the principles of international sales law, as set forth in the United Nations Convention on Contracts for the International Sale of Goods (CISG). These seminal pieces reflect various viewpoints of authors from different countries and legal systems, and offer a range of distinct methodological approaches to legal analysis. The review is an invaluable source of reference, providing the reader with both an international and an interdisciplinary perspective on the CISG and its application.